Potential of renewable surplus electricity for power-to-gas and geo-methanation in Switzerland. (5th May 2023) - Rüdisüli, Martin; Mutschler, Robin; Teske, Sinan L.; Sidler, Daniel; van den Heuvel, Daniela B.; Diamond, Larryn W.; Orehounig, Kristina; Eggimann, Sven
Abstract: Energy systems are increasingly exposed to variable surplus electricity from renewable sources, particularly photovoltaics. This study estimates the potential to use surplus electricity for power-to-gas with geo-methanation for Switzerland by integrated energy system and power-to-gas modelling. Various CO2 point sources are assessed concerning exploitable emissions for power-to-gas, which were found to be abundantly available such that 60 TWh surplus electricity could be converted to methane, which is the equivalent of the current annual Swiss natural gas demand. However, the maximum available surplus electricity is only 19 TWh even in a scenario with high photovoltaic expansion. Moreover, making this surplus electricity available for power-to-gas requires an ideal load shifting capacity of up to 10 times the currently installed pumped-hydro capacity. Considering also geological and economic boundary conditions for geo-methanation at run-of-river and municipal waste incinerator sites with nearby CO2 sources reduces the exploitable surplus electricity from 19 to 2 TWh. Highlights: Run-of-river power plants are best suited to allocate geo-methanation. Industrial CO2 is largely available and not constraining geo-methanation. An increase in load shifting power and capacity is required for power-to-gas. Transportation distanced between CO2 sources and geo-methanation site are short. Geology constraints the potential of combining power-to-gas and geo-methanation.